Liubov' i golubi - Menshov, Vladimir (Soviet Union, 1984)
Life in the remote Siberian village. Vasia, who has never left his family, comes to the Black Sea for a summer holiday. New world, new people - so, he's tempted by an eccentric woman. But after short time Vasia returns to his wife and children.